Deletion of astrocytic BMAL1 results in metabolic imbalance and shorter lifespan in mice. Issue 6 (13th December 2019) - Barca‐Mayo, Olga; Boender, Arjen J.; Armirotti, Andrea; De Pietri Tonelli, Davide
Abstract: Disruption of the circadian cycle is strongly associated with metabolic imbalance and reduced longevity in humans. Also, rodent models of circadian arrhythmia, such as the constitutive knockout of the clock gene Bmal1, leads to metabolic disturbances and early death. Although astrocyte clock regulates molecular and behavioral circadian rhythms, its involvement in the regulation of energy balance and lifespan is unknown. Here, we show that astrocyte‐specific deletion of Bmal1 is sufficient to alter energy balance, glucose homeostasis, and reduce lifespan. Mutant animals displayed impaired hypothalamic molecular clock, age‐dependent astrogliosis, apoptosis of hypothalamic astrocytes, and increased glutamate and GABA levels. Importantly, modulation of GABAA‐receptor signaling completely restored glutamate levels, delayed the reactive gliosis as well as the metabolic phenotypes and expanded the lifespan of the mutants. Our results demonstrate that the astrocytic clock can influence many aspects of brain function and neurological disease and suggest astrocytes and GABAA receptor as pharmacological targets to prevent the metabolic dysfunctions and shortened lifespan associated with alterations of circadian rhythms. Abstract : Astrocyte clock controls energy balance, glucose homeostasis and longevity in mice. Modulation of GABAA‐receptor signaling delays the metabolic phenotype and expanded the life span of mice with astrocytic deletion of BMAL1.